Barriers and limitations to national park visitation by millennials: Perceptions from second-generation Australians - Ngaire Griggs; Gary Terence Lacey (Annals of Tourism Research Empirical Insights, 2022)
Recent studies have suggested a trend of slowing domestic visitation to national parks by younger generations on a per capita basis within developed countries. This has often been attributed to inter-generational differences such as increased cultural diversity, interest in other forms of entertainment and lack of free time. The research employs the hierarchical model of leisure constraints to define interpersonal, intrapersonal, and structural barriers to the visitation of national parks. The findings of 26 in-depth qualitative interviews suggest complex relationships with natural environments. It was established that second-generation Australians were less likely to engage with national parks during childhood. However, this did not translate to a significant difference in perceived value or visitation rates in adulthood.
Keywords: 330; Place attachment; Multi-cultural engagement; Millennials; National parks; Leisure constraints theory; Australia